Monitoring the Kinetics of the Cellular Uptake of a Metal Carbonyl Conjugated with a Lipidic Moiety in Living Cells Using Synchrotron Infrared Spectromicroscopy. Issue 1 (January 2020) - Clède, Sylvain; Sandt, Christophe; Dumas, Paul; Policar, Clotilde
Presented here is the exploitation of synchrotron infrared spectromicroscopy to evaluate the feasibility of monitoring the cellular uptake of rhenium-tris-carbonyl-tagged (Re(CO)3 ) lipophilic chains in living cells. To this aim, an in-house thermostated microfluidic device was used to limit water absorption while keeping cells alive. Indeed, cells showed a high survival rate in the microfluidic device over the course of the experiment, proving the short-term biocompatibility of the device. We recorded spectra of single, living, fully hydrated breast cancer MDA-MB231 cells and could follow the penetration of the rhenium complexes for up to 2 h. Despite the strong variations observed in the uptake kinetics between individual cells, the Re(CO)3 complex was traced inside the cells at low concentration and shown to enter them on the hour time scale by active transport.